(untitled) (European Journal of Marketing and Economics, 2023)
The DSGE (Dynamic Stochastic General Equilibrium) methodology attempts to explain the behavior of aggregate economic phenomena, such as economic growth, business cycle, and the effects of monetary and fiscal policy, using macroeconomic models derived from microeconomic foundations. DSGE models study the economy evolution (dynamics) over time. They take into consideration the fact that economy may be affected with random (stochastic) shocks. Still, they include all markets in the economy and assume that those markets balance out rapidly (general equilibrium). DSGE models have become the main tool of macroeconomic analysis, and until now, a huge number of different DSGE models have been developed. They are used for forecasting, different economic policies analysis and giving policy advices. Due to data scarcity and lack of knowledge, indevelopment and many other reasnos, until now there was no application of DSGE models to Bosnia and Herzegovina case. That is why we were motivated to calibrate a small size DSGE model for Bosnia and Herzegovina. In this research we will calibrate a small open economy DSGE model for Bosnia and Herzegovina and use its results to give some advices for economic growth of Bosnia and Herzegovina improvement. The special attention will be given to Public expenditures and TFP influence on Bosnian macroeconomic variables.